PO 8573 Research, mentorship and sustainable development: is retirement age a hurdle to research sustainability in africa?. (24th April 2019) - Ngadaya, Esther; Kitua, Andrew; Castelnuovo, Barbara; Mmbaga, Blandina T; Mboera, Leonard; Kirenga, Bruce; Yimer, Getnet; Mukhtar, Maowia; Wandiga, Steve; Kwassi, Addo; Kazwala, Rudovick; Bonfoh, Bassirou; et al.
Abstract : Background: Retirement age in most of sub-Saharan Africa is between 55 and 60 years, even in academic and research institutions. There is no mechanism to retain even the few most experienced and outstanding among them. There is evidence that institutions retaining experienced researchers access better large research grants. Methods: We conducted literature review and shared views and experiences among peer research scientists Results: Most African scientists obtain their first degrees aged 25–30 years. Economic needs compounded with work experience requirements for PhD studies delay their research career development such that most PhD graduates are 40–50 years of age. However, unlike in the developed world where the majority acquire their PhDs in their late 20's or early 30's, there is no mechanism to retain them longer at work to maximise their contributions to scientific developments. Instead, African scientists are forced to retire young at 60 years of age. On the contrary, developed countries scientists graduate earlier, work longer and have retention mechanisms even after retirement. African countries do not consider retaining even the few who have demonstrated outstanding performance. Consequently, outstanding research scientists retire at the time when they are needed most. They seek and get jobs abroad or in externally owned projects (brain drain). Their decade or so of work, generates more resources abroad, depriving Africa of resource generating capacity. Secondly, retiring at the height of their performance is economically counterproductive. Thirdly, this affects negatively the career development of young scientists for lack of experienced supervisors and mentors. Conclusion: Africa must rethink the retirement age of its research scientists and create incentives to retain outstanding research scientists who reach retirement age. This is urgently needed to stop brain drain, contribute to economic development, and accelerate ongoing efforts to build sustainable research capacity and mentorship programmes in Africa.